The demographics of patients affected by surgical disease in district hospitals in two sub-Saharan African countries: a retrospective descriptive analysis. - Grimes, C; Billingsley, M; Dare, A; Day, N; George, P; Kamara, T; Mkandawire, N; Leather, A; Lavy, C (SpringerOpen, 2015)
There is a growing awareness of the importance of surgical disease within global health. We hypothesised that surgical disease in low income countries predominantly affects young adults and may therefore have a significant economic impact.We retrospectively reviewed all surgical admission data from two rural government district hospitals in two different sub-Saharan African countries over a 6-month period. We analysed all surgical admissions with respect to patient demographics (age and gender), diagnosis, and procedure performed.Surgical admissions accounted for 12.9 and 19.8 % of all hospital admissions in Malawi and Sierra Leone respectively. 18.5 and 6.2 % of all hospital patients required a surgical procedure in Malawi and Sierra Leone respectively, with the low number in Sierra Leone accounted for in that many of the obstetric admissions were referred to a nearby Medicins Sans Frontiers (MSF) hospital for treatment. 17.9 and 10.5 % of surgical admissions were under the age of 16 in Malawi and Sierra Leone respectively, with 16-35 year olds accounting for 57.3 % of surgical admissions in Sierra Leone and 53.5 % in Malawi. Men accounted for 53.7 and 46.0 % of surgical admissions in Sierra Leone and Malawi respectively. An unexpected finding was the high level of patients who absconded from hospital in Sierra Leone after diagnosis but before treatment. This involved 11.8 % of all surgical patients, including 38 % with a bowel obstruction, 39 % with peritonitis and 20 % with ectopic pregnancy.Most people affected by disease requiring surgery are young adults and this may have significant economic implications.